(untitled) (Journal of the College of Basic Education, 2022)
The research covered five chapters; Chapter One: guarantees provided and the importance of research and the research problem under study and the goals of research which determine the effect of the style of the competitive team to learn the long-handling over the shoulder of basketball skill, knowledge of the extent of the influence of the style of the competitive team to learn the skill of clapotement change the direction of basketball, either hypotheses are. -The presence of statistically significant differences between the results of the tests and the results of the tribal post tests for the two experimental and control group to learn the handling of the above shoulder 0 skill differences. -The presence of statistically significant differences between the results of the tests and the results of the tribal post tests for the two experimental and control group differences to learn a skill clapotement change direction . -And no statistically significant differences between the results of the post tests of the experimental and control groups to learn my skills over the handling of the shoulder and clapotement change direction . And ensure that the human and the temporal and spatial domains . The second chapter guarantees the address to the learning style of the competitive collective skills and basic basketball clapotement change direction and handling over the shoulder . The third chapter guarantees the research methodology was used experimental method and sample one of the students of the first stage of Education, Department of Sports College of Basic Mustansiriya University education and the number of the sample ( 60) students were divided into two groups, the experimental group (30) students and the control group (30) students, as well as ensure tools and the means used for research and testing skills and the scientific foundations for the tests and tests tribal and ensure the application of competitive learning style of collective posteriori tests and statistical methods The fourth chapter included a presentation and analysis and discussion of the results tribal tests and a posteriori for the two experimental and control of Mhartin handling over the shoulder and clapotement change direction . The fifth chapter guarantees the conclusions and recommendations reached by the researcher, namely 1-The style of learning the competitive mass has a positive effect on the learning and development of the level of performance skills in handling my skills over the shoulder and clapotement change the direction of basketball. 2-The results showed the effectiveness of competition in the style of collective learning my skills handling with one hand and clapotement change the direction of basketball. The recommendations Vtdment; 1-Emphasize the use of collective style competition to learn the basic skills of basketball on the academic level. 2-Adoption of the collective style of competition, along with teaching practice in learning the basic skills of basketball.